Thyroid-stimulating hormone, thyroglobulin, and thyroid hormones and risk of differentiated thyroid carcinoma: the EPIC study. - Rinaldi, S; Plummer, M; Biessy, C; Tsilidis, K; Østergaard, J; Overvad, K; Tjønneland, A; Halkjaer, J; Boutron-Ruault, M; Clavel-Chapelon, F; Dossus, L; Kaaks, R; et al. (Oxford University Press, 2014)
BACKGROUND: Increased levels of thyroglobulin (Tg) and thyroid-stimulating hormone (TSH) are associated with differentiated thyroid carcinoma (TC) risk, but strong epidemiological evidence is lacking. METHODS: Three hundred fifty-seven incident TC case patients (n = 300 women and 57 men; mean age at blood collection = 51.5 years) were identified in the EPIC cohort study and matched with 2 (women) or 3 (men) control subjects using incidence density sampling. Matching included study center, sex, age, date, time, and fasting status at blood collection. Levels of total and free (f) thyroxine (T4) and triiodo-thyronine (T3), TSH, Tg, and anti-Tg antibodies (TgAb) were measured by commercially available immunoassays. Odds ratios (ORs) and 95% confidence intervals (CIs) were computed using conditional logistic regression. All statistical tests were two-sided. RESULTS: TC risk was positively associated with Tg (OR for the highest vs lowest quartile = 9.15; 95% CI = 5.28 to 15.90; P < .001) and negatively associated with TSH level (OR = 0.56; 95% CI = 0.38 to 0.81; P = .001). Odds ratios were not modified by adjustment for weight and height and were consistent across sexes, age groups, and countries. The association with Tg was stronger in follicular than papillary TC. The odds ratio for TgAb-positivity was 1.50 (95% CI = 1.05 to 2.15; P = .03). Among case patients, TSH level was stable over time, whereas Tg level was higher in proximity to TC diagnosis. Areas under the receiver operating characteristic curve were 57% and 74% for TSH and Tg level, respectively. CONCLUSIONS: High Tg levels precede by up to 8 years the detection of TC, pointing to a long sojourn time of the disease. Low TSH levels may predispose to TC onset. Neither marker has sufficient accuracy to be a screening test.